Transformation of Marketing Management of Private Institutions in the Era of Global Competition - Al Fawaz, Ahmad Hadiq Syifa; Purnomo, Muhammad Sidiq (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aims to provide a comprehensive understanding of the evolving preferences of education consumers and the strategic transformations private education institutions require to remain competitive in a globalized environment. The study uses a qualitative approach and a case study design to examine how consumer preferences have changed and how private educational institutions have adjusted their marketing tactics in response to international competition. Data collection techniques were in-depth interviews, document analysis, and marketing practice observations. Triangulation techniques were applied to ensure data validity, while thematic analysis was used to uncover patterns and key themes. The findings reveal a significant shift towards global skills-based education preferences, highlighting the critical role of digitalization in educational marketing and the challenges posed by accessibility gaps resulting from commercialization. Despite the potential of technology to broaden access and enhance transparency, high costs remain a substantial barrier for many. The study underscores the necessity of collaboration among governments, private sectors, and non-profit organizations to formulate inclusive policies that guarantee equitable access to quality education. The insights and strategic frameworks derived from this research offer valuable guidance for institutions seeking to navigate the dynamic landscape of global education.